Progress of studies on sclerostin’s role in vascular calcification of chronic kidney disease - PENG Qiong-yao; LIU Ling (Linchuang shenzangbing zazhi)
As an essential messenger between bones and vessel axis,sclerostin plays a key role in development and progression of vascular calcification;however,its mechanism is complicated.Current studies have demonstrated,sclerostin is an osteocyte-specific glycoprotein,which is considered as an effective inhibitor of bone formation;its biological effects are exerted by inhibiting the specific co-receptors required for Wnt/β-catenin signaling activation.Thus,serum sclerostin levels may reflect bone metabolism,and may be used as a marker of low and middle turnover bone disease and renal osteodystrophy in patients with end stage renal disease(ESRD).In spite of this,anti-sclerostin antibodies may be a novel therapy.This article is supposed to understand basic structure and biological activity of sclerostin,meanwhile review its relationship with chronic kidney diseases and vascular calcification,and comp up with application of anti-sclerostin antibody therapy in patients with CKD.